An unexpected metal-free DMAP catalyzed Michael addition–elimination domino reaction between 2-naphthols and bromomaleimides for the effective construction of 3-arylmaleimides. Issue 11 (16th March 2016) - Zhang, Yong; Chen, Feng; Yang, Yu; Tang, Chao-Zhe; Tian, Fang; Peng, Lin; Wang, Li-Xin
Graphical abstract: An unexpected novel DMAP catalyzed Michael addition–elimination domino reaction between 2-naphthols and bromomaleimides has been reported. This protocol features metal-free catalysis and mild reaction conditions, which furnished 3-aryl maleimides in moderate to excellent yields (25–89% yields). Abstract: An unexpected novel DMAP catalyzed Michael addition–elimination domino reaction between 2-naphthols and bromomaleimides has been reported. This protocol features metal-free catalysis and mild reaction conditions, which furnished 3-arylmaleimides in moderate to excellent yields (25–89% yields).